OPEN CLUSTERS AND FIELD CEPHEIDS IN THE GALACTIC DISK – CONTRADICTIONS IN PROPERTIES - Marsakov, V. A.; Koval’, B. B.; Gozha, M. I.; Kovtyukh, V. V.; Mishenina, T. V. (Одеські астрономічні публікації, 2013)
The comparative analysis of the abundances of α-process elements, elements of the rapid and the slow neutron capture and iron in the open stellar clusters, field Cepheids, and also in red giants and dwarfs of the thin disk has been performed. The found distinctions and the revealed regularities are attracted for clarification of the history of star formation in the thin disk of the Galaxy.